Unusual Features of Pomoviral RNA Movement - Torrance, Lesley; Wright, Kathryn; Crutzen, Francois; Cowan, Graham; Lukhovitskaya, Nina; Bragard, Claude; Savenkov, Eugene (Frontiers in Microbiology, 2011)
Potato mop-top pomovirus (PMTV) is one of a few viruses that can move systemically in plants in the absence of the coat protein (CP). Pomoviruses encode the triple gene block genetic module of movement proteins (TGB 1, 2 & 3) and recent research suggests that PMTV RNA is transported either as ribonucleoprotein (RNP) complexes containing TGB1 or encapsidated in virions containing TGB1. Furthermore, there are different requirements for local or systemic (long distance) movement. Research suggests that nucleolar passage of TGB1 may be important for the long distance movement of both RNP and virions. Moreover, and uniquely, the long distance movement of the CP-encoding RNA requires expression of both major and minor CP subunits and is inhibited when only the major CP sub unit is expressed. This paper reviews recent pomovirus research and presents a current model for RNA movement.